Mengukur Kualitas Dialogis 13 Website PTN-BH Melalui Penerapan Dialogic Communication - Lisda Veronika; Reza Safitri; Rachmat Kriyantono (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Public relations as the communication management between organization and its public has entered a new chapter with new challenges at this time. The development of information and communication technology encourages public relations to be able to take advantage of various new media in carrying out its strategic communications. Website as a product of new media is often used as a formal information medium for an organization. Not only SOE or the private sector, educational institutions or universities have also used website as a medium of their formal information and communication. The capabilities of websites 1.0 to 4.0, which continue to grow to this day, allow companies and their public to communicate in two directions, or dialogical. This study aims to determine the dialogic quality of the PTN-BH website through dialogic communication theory.